EVALUASI SISTEM USABILITY SCALE GUNA REDESIGN WEBSITE SMAN 1 KARAWANG MENGGUNAKAN USER CENTERED DESIGN - Yayan Mulyana; Raffi Naufal Fahreza; Pascalis Ernesto Rana; Garno (Jurnal Mahasiswa Sistem Informasi (JMSI), 2026)
This study focuses on the field of Human Computer Interaction (HCI) and aims to evaluate the usability level and redesign the user interface of the SMAN 1 Karawang website to improve user experience. The problem addressed is the low level of usability, as indicated by unclear navigation, unstructured layout, and inconsistent interface design. Based on the initial evaluation using the System Usability Scale (SUS) involving 20 respondents, an average score of 61.625 was obtained, indicating that the system was still in the marginal category. The methods used in this study are the System Usability Scale (SUS) for usability evaluation and the User Centered Design (UCD) approach for the redesign process. The results show that after the interface redesign, usability improved significantly and reached the acceptable category. Therefore, the implementation of SUS and UCD methods is proven to be effective in improving usability and user experience on the SMAN 1 Karawang website.